CORRECTION FOR VOLATILE FRACTIONATION IN ASCENDING MAGMAS: NOBLE GAS ABUNDANCES IN PRIMARY MANTLE MELTS - Burnard P. (My University, 2001)
Accurate relative noble gas abundances of mantle-derived melts are required in order to further understand the distribution of noble gases in the mantle and fractionation of noble gases during the melting process. Noble gas relative abundances in the majority of oceanic basalts are highly fractionated, at least in part due to late stage, solubility controlled fractionation. Noble gas concentrations in the volatile phase (≡ noble gas:CO2 ratio) will vary systematically during solubility controlled degassing of a magma. This contribution models the noble gas concentrations in the volatile phase during degassing at different pressures and vesicularities in order to develop a method for correcting fractionation resulting from magmatic degassing, and thereby estimate the “initial” (pre-degassing) noble gas compositions.